FEA ANALYSIS OF FRICTIONAL HEATING PROCESS (FRICTION HEAT VS. LINEAR VELOCITY) (International Journal of Engineering Sciences & Management Research, 2016)
In the present model only heat generation due to friction is considered. Three-dimensional nonlinear thermal numerical simulations are conducted for the friction stir welding (FSW) of 304L material.Friction stir welding – FSW was a promising welding technology because of its easy use, low energy costs, being ecology friendly process and with no need for filler metal. The aim of the study is to find the heat generated during frictional process. It will help to find trend for the relationship between rotation speed of the tool, translational velocity of tool and the maximum temperature of the welding process. The aim is to create a simple, fast and accurate friction simulation model without the need of complex computational power or knowledge of precise process data.